2020
DOI: 10.1097/pr9.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Age does not affect sex effect of conditioned pain modulation of pressure and thermal pain across 2 conditioning stimuli

Abstract: Introduction: Conditioned pain modulation (CPM) is a laboratory test resulting in pain inhibition through activation of descending inhibitory mechanisms. Older adults consistently demonstrate reduced CPM compared with younger samples; however, studies of sex differences in younger cohorts have shown mixed results. Objectives: This study tested for sex differences in CPM within samples of younger and older adults. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…Age only had influence on CPM at the m. trapezius with the CPA as conditioning stimulus, however, the age range in the present study was relatively small, and the mean age indicated a rather young sample. The weakest CPM‐effect was found in older females (Riley et al., 2020). In the current study there were only six participants (four women) above 40 years, which explains the limited influence of age.…”
Section: Discussionmentioning
confidence: 99%
“…Age only had influence on CPM at the m. trapezius with the CPA as conditioning stimulus, however, the age range in the present study was relatively small, and the mean age indicated a rather young sample. The weakest CPM‐effect was found in older females (Riley et al., 2020). In the current study there were only six participants (four women) above 40 years, which explains the limited influence of age.…”
Section: Discussionmentioning
confidence: 99%
“…Average pain last week (0-10 NRS) Total score 7 [7,8] 19 [13,23] 7.5 [6,9] 18 [12,24] 7 [7,8] 18 [13,19] 7 [7,8] 22 [19,24] McGill Pain Questionnaire Sensory (0-33) 15 [12,18.5] 15.5 [12,18.8] 14 [9,19] 15. 5 [13,17.3] Affective (0-12) 4 [2,6] 3.5 [1.3,5] 4 [2,6] 4 [3,6] [4,19] n=19 25 [18,40] n=19 42 [27,56] n=13 14 [3,16] 31 [18,36] Data presented as mean±SD, (%), median [IQR 25 th , 75 th percentile], or n (%).…”
mentioning
confidence: 99%
“…Although the proportion of males and females in our study was not significantly different between groups, the healthy group was significantly younger than the chronic pain group. Interestingly, a recent study in healthy individuals found the age effect was larger than the sex effect; across all the different stimulus modality paradigms younger males had the strongest inhibitory CPM ( 32 ). This aligns with previous findings showing that younger and healthy individuals on average have a stronger inhibitory CPM than older individuals and those with chronic pain ( 13 ).…”
Section: Discussionmentioning
confidence: 92%